2020
DOI: 10.7861/clinmed.2020-0232
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic intracranial hypertension: Update on diagnosis and management

Abstract: Idiopathic intracranial hypertension is a condition of raised intracranial pressure of unknown cause. Features include new onset headache, which is frequently non-specific; papilloedema is present, visual disturbances are common; and there may be sixth nerve palsy. Diagnosis includes brain imaging with venography to exclude structural causes and venous sinus thrombosis. Lumbar puncture reveals pressure greater than 250 mmCSF with normal constituents. Treatments aim to modify the disease, prevent permanent visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 33 publications
0
32
0
5
Order By: Relevance
“…When compared to the primary care data in the UK, which have previously been published, the incidence over corresponding years is similar. [ 4 ] Likewise, within this cohort there are patients over the age of 65 years ( Figure 2 A), which is not typical of the known phenotype of IIH, described by the IIH literature as a disease that occurs with the major risk factor being weight gain in women of working age [ 1 , 2 , 7 ]. A recent retrospective case series analysis of IIH above the age of 65 years reported that the diagnosis was more commonly seen in males, with incidentally found papilloedema; they had fewer headaches, and on investigation had lower lumbar puncture opening pressure, as compared to IIH controls below the age of 50 years [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When compared to the primary care data in the UK, which have previously been published, the incidence over corresponding years is similar. [ 4 ] Likewise, within this cohort there are patients over the age of 65 years ( Figure 2 A), which is not typical of the known phenotype of IIH, described by the IIH literature as a disease that occurs with the major risk factor being weight gain in women of working age [ 1 , 2 , 7 ]. A recent retrospective case series analysis of IIH above the age of 65 years reported that the diagnosis was more commonly seen in males, with incidentally found papilloedema; they had fewer headaches, and on investigation had lower lumbar puncture opening pressure, as compared to IIH controls below the age of 50 years [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the relative rarity of IIH the multidisciplinary manifestations of the condition lead these patients to access hospital care though a large number of hospital specialties. Headache is the predominant morbidity in over 90% [ 2 , 6 ] and persistent post-IIH headache a challenge to manage [ 7 , 8 ]. Sight loss is not uncommon as typically 7% will require surgical intervention to save vision [ 3 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent medication used in treating IIH, acetazolamide, is unspecific and is not well tolerated, causing up to half of the patients to discontinue their treatment [ 39 , 40 ]. Topiramate has been tested in an animal study and seemed more efficient than acetazolamide to reduce ICP but so far no randomized controlled human studies are available [ 41 ].…”
Section: Management and Follow-upmentioning
confidence: 99%
“…For many patients topiramate reduces appetite—a side effect than can be helpful in weight reduction. However, adherence to topiramate are likewise hampered by significant side effects as paresthesia, nausea, sedation, taste alteration and kidney stones and cognitive impairment [ 39 , 40 ]. Careful education in symptoms and signs is therefore of immense value for these patients as adherence to medical treatment can be determinant for the beneficial outcome.…”
Section: Management and Follow-upmentioning
confidence: 99%
“…Most can be picked up remotely through systematic questioning (for example sudden onset, worsening or visual symptoms, scalp and temporal tenderness, jaw claudication) and patient access to thermometers and home sphygmomanometers aid assessment. In people with headache, elevated BMI and visual symptoms, urgent ophthalmological assessment is needed, looking for idiopathic intracranial hypertension as headache features may overlap with migraine [ 36 ]. Ophthalmologists and opticians have adapted safe modes of eye examination suitable for the pandemic [ 37 ].…”
Section: Missing the Diagnosis Of Secondary Headachementioning
confidence: 99%